(untitled) (Bangladesh Journal of Microbiology, 2010)
Previously, we have reported that the PhoP-PhoQ two-component system (TCS) is essential for synthesis of pectate lyase, resistance to antimicrobial peptide and accumulation of acetyl-coenzyme A in Dickeya dadantii 3937. In this study, marker-exchange mutagenesis of phoP and phoQ of D. dadantii 3937 resulted in loss of virulence in Chinese cabbage and a severe reduction of bacterial population in infected area and its surrounding healthy tissue was also seen. Inoculation of bacteria grown and re-suspended in medium containing low concentration of Mg2+ resulted in reduced virulence and significantly reduced bacterial population in wild type while these mutants showed higher virulence and higher bacterial populations at high Mg2+ condition. Since Mg2+ concentration was detected to be very low (14.6 ± 4.23/100 g) in the apoplastic fluids of Chinese cabbage thus, the PhoP-PhoQ two-component system of D. dadantii 3937 is compromised virulence, at least in part, due to colonization of bacteria in planta responding to Mg2+. Keywords: Virulence; Bacterial population; Magnesium, Dickeya dadantii DOI: http://dx.doi.org/10.3329/bjm.v25i1.4853 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 36-40